A 3D Printed Implantable Device for Voiding the Bladder Using Shape Memory Alloy (SMA) Actuators. Issue 11 (26th July 2017) - Hassani, Faezeh Arab; Peh, Wendy Yen Xian; Gammad, Gil Gerald Lasam; Mogan, Roshini Priya; Ng, Tze Kiat; Kuo, Tricia Li Chuen; Ng, Lay Guat; Luu, Percy; Yen, Shih‐Cheng; Lee, Chengkuo
Abstract: Underactive bladder or detrusor underactivity (DU) is defined as a reduction of contraction strength or duration of the bladder wall. Despite the serious healthcare implications of DU, there are limited solutions for affected individuals. A flexible 3D printed implantable device driven by shape memory alloys (SMA) actuators is presented here for the first time to physically contract the bladder to restore voluntary control of the bladder for individuals suffering from DU. This approach is used initially in benchtop experiments with a rubber balloon acting as a model for the rat bladder to verify its potential for voiding, and that the operating temperatures are safe for the eventual implantation of the device in a rat. The device is then implanted and tested on an anesthetized rat, and a voiding volume of more than 8% is successfully achieved for the SMA‐based device without any surgical intervention or drug injection to relax the external sphincter. Abstract : A novel flexible actuating device driven by shape memory alloy wires is developed and tested in a benchtop setup to study its potential in physically contracting a rubber replica of a bladder. The device is then implanted successfully in an anesthetized animal. This device can potentially help affected individuals with detrusor muscle atrophy to achieve facilitated micturition.